Beyond Ethical Fashion: Can Milanese Designers Foster True Economic Independence for Sierra Leonean Artisans? - Wang Ronghan,; Li Wenjing,; Yao Dehe, (European Journal of Sustainable Development, 2025)
This study critically examines SIERRA2go, a Milan-based, designer-led non-profit initiative that collaborates with female artisans in Sierra Leone. Positioned within the discourse of sustainable fashion and economic empowerment, SIERRA2go presents itself as an alternative to profit-driven fair-trade models by relying on external funding and training programs rather than direct market sales. While the initiative aspires to foster long-term independence for artisans, key questions remain: Does it truly empower them, or does it subtly reinforce dependence on Western markets? Drawing on perspectives from cultural capital theory, postcolonial fashion studies, and economic ethics in sustainable fashion, this study explores SIERRA2go’s impact on market access, production control, and financial sustainability. The findings suggest that while SIERRA2go offers a refreshing alternative to traditional fair trade, its reliance on donor funding may ultimately limit artisans’ economic autonomy rather than strengthen it. This paper argues that for true empowerment to occur, locally driven business models and direct market access strategies must be prioritized—otherwise, well-intended interventions risk perpetuating the very dependency they seek to dismantle. Keywords: Sustainable Fashion, Economic Empowerment, Milanese Design, Artisanal Training, Non-Profit Model, Postcolonial Fashion